Pelatihan Dan Pendampingan Perhitungan Harga Pokok Produksi (HPP) Dalam Menunjang Kesuksesan UMKM Di Kelurahan Klampis Ngasem - Galuh Kinanti; Nuril Nadi’a Aditia; Roziana Febrianita (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The community service activity was carried out by the East Java UPNV KKNT-T team in Klampis Ngasem Village with the background from the results of the Forum Group Discussion for MSMEs in Klampis Ngasem Village including: lack of knowledge regarding Cost of Production, lack of knowledge regarding classification and cost calculation fixed and variable costs in accordance with Generally Accepted Accounting Principles both manually andexcel. The purpose of holding this activity is that MSME actors in Klampis Ngasem Village have knowledge and understanding regarding the calculation of the Cost of Production so that they are able to determine a good selling price and get the expected profit. The methods used in this community service activity are observation, problem-solving approaches, training, and mentoring. The results of the implementation of this service are as follows: exposure, training, and assistance regarding fixed costs and variable costs have been carried out so that they are able to carry out the principles of calculating in accordance with Generally Accepted Accounting Principles.